Rebranding exercise: closing the gap between values and behavior - Eccles Jacquelynne S; Segar Michelle L; Richardson Caroline R (BMC, 2011)
Abstract Background Behavior can only be understood by identifying the goals to which it is attached. Superordinate-level goals are linked to individuals' values, and may offer insights into how to connect exercise with their core values and increase participation in sustainable ways. Methods A random sample of healthy midlife women (aged 40-60y) was selected to participate in a year-long mixed-method study (n = 226). Superordinate goals were measured inductively and analyzed using grounded theory analysis. Attainment Value and Exercise Participation were quantitatively measured. An ANOVA and pairwise comparisons were conducted to investigate the differences between superordinate exercise goals in attainment value. This study fit a Linear Mixed Model to the data to investigate the fixed effects of superordinate goals on exercise participation, controlling for BMI and social support. Results Participants mainly exercised to achieve Healthy-Aging, Quality-of-Life, Current-Health, and Appearance/Weight superordinate goals. Despite equally valuing Healthy-Aging, Quality-of-Life, and Current-Health goals, participants with Quality-of-Life goals reported participating in more exercise than those with Current-Health (p < 0.01), and Healthy-Aging (p = 0.06) goals. Conclusions Superordinate exercise goals related to health and healthy aging are associated with less exercise than those related to enhancing daily quality of life, despite being equally valued. While important, pursuing distant benefits from exercise such as health promotion, disease prevention, and longevity might not be as compelling to busy individuals compared to their other daily priorities and responsibilities. By shifting our paradigm from medicine to marketing, we can glean insights into how we can better market and "sell" exercise. Because immediate payoffs motivate behavior better than distant goals, a more effective "hook" for promoting sustainable participation might be to rebrand exercise as a primary way individuals can enhance the quality of their daily lives. These findings have important implications for how we as a culture, especially those in fitness-related businesses, health promotion, health care, and public health, prescribe and market exercise on individual and population levels.